A REVIEW ON METHODS AND CASE STUDIES ON CARBON SEQUESTRATION POTENTIAL OF URBAN-GREEN AREAS (International Association of Biologicals and Computational Digest, 2023)
Urban-green areas provide various ecosystem services; one such service is that tree species lower the temperature in the atmosphere and have tremendous potential to sequent carbon. The present review particularly focuses on the different methods used for above-ground biomass estimation. Two methods, field methods (destructive and non-destructive), and remote sensing methods (optical remote sensing, RADAR, and LiDAR) are used for biomass estimation. It has been found that all these methods have some advantages and limitations. In addition to this, we have reviewed various case studies of urban tree species' potential to sequester carbon dioxide.
Keywords: Above-ground biomass, Carbon sequestration, Urban-green areas